2020
DOI: 10.4236/ojts.2020.101002
|View full text |Cite
|
Sign up to set email alerts
|

Amiodarone for Postoperative Atrial Fibrillation in Lung Cancer Patients: A 6-Year Follow-Up Study

Abstract: Background: The preventive effect of prophylactic amiodarone on postoperative atrial fibrillation (POAF) in patients undergoing thoracic surgery has previously been demonstrated. Meanwhile, the long-term effect remains unknown. We investigated the long-term effect of prophylactic amiodarone, in patients undergoing surgery for lung cancer, along with the long-term prognosis of patients with POAF within 6 years of follow-up. Methods: Using data from national databases, we retrospectively analysed 250 patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Because AF is common in LC patients in the perioperative period, a number of studies have examined the use of antiarrhythmic drugs to prevent its occurrence. Some studies have shown that intravenous amiodarone, followed by oral administration for several days, is effective and safe in patients undergoing lung cancer surgery [42][43][44]. The addition of N-acetylcysteine to amiodarone had no additional beneficial effect [45].…”
Section: Management Of Supraventricular Arrhythmias In Lung Cancer Pa...mentioning
confidence: 99%
“…Because AF is common in LC patients in the perioperative period, a number of studies have examined the use of antiarrhythmic drugs to prevent its occurrence. Some studies have shown that intravenous amiodarone, followed by oral administration for several days, is effective and safe in patients undergoing lung cancer surgery [42][43][44]. The addition of N-acetylcysteine to amiodarone had no additional beneficial effect [45].…”
Section: Management Of Supraventricular Arrhythmias In Lung Cancer Pa...mentioning
confidence: 99%